A Genetic Basis for Motivated Exercise. Issue 4 (October 2015) - Good, Deborah J.; Li, Mengjiao; Deater-Deckard, Kirby
Abstract : Prior research has demonstrated a genetic basis for motivated exercise, with evidence of a role for nescient helix-loop-helix-2 (NHLH2/Nhlh2). Nhlh2 transcriptionally regulates the monoamine oxidase A (MAO-A) gene. This article examines the evidence for the hypothesis that polymorphisms in NHLH2 or MAO-A contribute to differences in the human motivation for exercise and physical activity. The genetic pathways that link exercise and motivation are discussed. Abstract : Can the genetic basis for motivated exercise be linked to a single neural pathway?